Let P ( x ) be a nonzero polynomial such that ( x − 1 ) P ( x + 1 ) = ( x + 2 ) P ( x ) for every real x , and ( P ( 2 ) ) 2 = P ( 3 ) . Then find P ( 2 0 1 6 ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
That's was my alternate solution. Nice one.
Is there any method or by hit and trial to calculate a general trend of P ( x − 1 P ( x ) = ( x − 2 ) ( x + 1 ) ?
Log in to reply
I dont think there's a general approach but we need to spot out recursions in problems so as to telescope the products.
From the equation we see that
( x + 2 ) ∣ P ( x + 1 ) ( x − 1 ) ∣ P ( x )
and from here we can see that
( x + 1 ) ∣ P ( x ) . This means that 1 and − 1 are roots of P ( x ) . Plug in x = 0 and we see that P ( 0 ) = 0 so 0 is also a root.
Suppose we had another root that is not one of those 3 . Notice that the equation above indicates that if r is a root then r + 1 and r − 1 is also a root. Then we'd get an infinite amount of roots! So that is bad. So we cannot have any other roots besides those three.
This means that P ( x ) = c x ( x − 1 ) ( x + 1 ) . We can use P ( 2 ) 2 = P ( 3 ) to get c = 3 2 . Plugging in 2 0 1 6 is now trivial and we see that it is
P ( 2 0 1 6 ) = 3 2 × 2 0 1 6 × 2 0 1 5 × 2 0 1 7 = 5 4 6 2 3 5 8 7 2 0 .
Awesome prob+solution.
We have x − 1 dividing P ( x ) and x + 2 dividing P ( x + 1 ) , so that x + 1 divides P ( x ) as well. If we write P ( x ) = ( x − 1 ) ( x + 1 ) Q ( x ) , then ( x − 1 ) x ( x + 2 ) Q ( x + 1 ) = ( x + 2 ) ( x − 1 ) ( x + 1 ) Q ( x ) and hence x Q ( x + 1 ) = ( x + 1 ) Q ( x ) , so that x + 1 Q ( x + 1 ) = x Q ( x ) and hence Q ( x ) = A x . Since P ( 2 ) 2 = P ( 3 ) it follows that A = 3 2 , so that P ( x ) = 3 2 x ( x − 1 ) ( x + 1 ) , which makes P ( 2 0 1 6 ) = 5 4 6 2 3 5 8 7 2 0 .
function it();
p=80;
for k=6 to 2016 do
p=p*(k+1)/(k-2);
end
return(p);
Function call: it()
ans22 = 5462358720.00000
Problem Loading...
Note Loading...
Set Loading...
Since plugging x = 2 gives the values P ( 2 ) = 4 & P ( 3 ) = 1 6 and we have the relation P ( x ) P ( x + 1 ) = x − 1 x + 2
A set of relations show P ( x − 1 ) P ( x ) = x − 2 x + 1 , P ( x − 2 ) P ( x − 1 ) = x − 3 x , ⋯ , P ( 2 ) P ( 3 ) = 4 and multiplying all of them we get P ( x ) = P ( 3 ) 2 . 3 . 4 ⋯ ( x − 2 ) 5 . 6 . 7 . 8 ⋯ ( x + 1 ) = 4 ( 3 x + 1 )
Thus P ( 2 0 1 6 ) = 5 4 6 2 3 5 8 7 2 0 follows.